ANALYSIS ON APPLICATIONS OF OPTICCAL FIBER ON BRILLOUIN SCATTERING PHENOMENA - Madhavi, M. (The journal of contemporary issues in business and government, 2022)
It has been demonstrated that Raman distributed optical fibre sensing is a mature and versatile scheme that provides a great deal of flexibility and effectiveness for the distributed temperature measurement of a wide range of engineering applications. This is an advantage that Raman distributed optical fibre sensing has over other established techniques. Over the course of the last few decades, this technology has undergone a period of rapid development and has found widespread use in fields ranging from industrial manufacture to scientific research. On the other hand, classical Raman distributed optical fibre sensing suffers from the following four conceptual or technical limitations: (i) The accuracy of the system's temperature measurement is hindered by a difference in the Raman optical attenuation, a low signal-to-noise ratio (SNR) of the system, and a fixed error in the Raman demodulation equation. ii) There is an incompatibility between the sensing distance and the spatial (iii) The SNR of the system and the measurement time of the system are in direct opposition to one another. (iv) Dual-parameter detection cannot be carried out using Raman distributed optical fibre sensing. This article presents a review of recent developments in performance enhancements and typical applications of Raman distributed optical fibre sensing. These developments are based on the theoretical and technical bottlenecks described above. The performance and accuracy of these systems can be improved by integrating the technology of this optical system with other knowledge-based technologies, such as demodulation technology, for example.